Human Epididymis Secretory Protein 4 (HE4) Compromises Cytotoxic Mononuclear Cells via Inducing Dual Specificity Phosphatase 6 - James, Nicole E.; Oliver, Matthew T.; Ribeiro, Jennifer R.; Cantillo, Evelyn; Rowswell-Turner, Rachael B.; Kim, Kyu-Kwang; Chichester, Clinton O.; DiSilvestro, Paul A.; Moore, Richard G.; Singh, Rakesh K.; Yano, Naohiro; Zhao, Ting C. (Frontiers in Pharmacology, 2019)
SWhile selective overexpression of serum clinical biomarker Human epididymis secretory protein 4 (HE4) is indicative ofovarian cancer tumorigenesis, much is still known about the mechanistic role of the HE4 gene or gene product. Here, we examine the role of the secretory glycoprotein HE4 in ovarian cancer immune evasion. Through modified subtractive hybridization analyses of human peripheral blood mononuclear cells (PBMCs), we have characterized gene targets of HE4 and established a preliminary mechanism of HE4-mediated immune failure in ovarian tumors. Dual specificity phosphatase 6 (DUSP6) emerged as the most upregulated gene in PBMCs upon in vitro exposure to HE4. DUSP6 was found to be upregulated in CD8+ cells and CD56+ cells. HE4 exposure reduced Erk1/2 phosphorylation specifically in these cell populations and the effect was erased by co-incubation with a DUSP6 inhibitor, (E)-2-benzylidene-3-(cyclohexylamino)-2,3-dihydro-1H-inden-1-one (BCI). In co-culture with PBMCs, HE4-silenced SKOV3 human ovarian cancer cells exhibited enhanced proliferation upon exposure to external HE4, while this effect was partially attenuated by adding BCI to the culture. Additionally, the reversal effects of BCI were erased in the co-culture with CD8+ / CD56+ cell deprived PBMCs. Taken together, these findings show that HE4 enhances tumorigenesis of ovarian cancer by compromising cytotoxic CD8+ and CD56+ cells through upregulation of self-produced DUSP6.